ACAN SPEED, ATTACK ANGLE AND CUTTING FORCE, AFFECT THE QUALITY OF SUGARCANE HARVEST? - Dos Santos Moura, Michel; Carpes, Aldir; Grudtner, Guinther Hugo; Lanças, kléber Pereira (Revista Brasileira de Engenharia de Biossistemas, 2021)
The base cut of cultures is one of the most studied parameters, and the variables involved in this process should be better evaluated under controlled conditions. The aim of this study was to evaluate, using an electromechanical device, under controlled conditions, the influence of the cutting angle and the machine's translation speed on the impact force generated on sugarcane stalks in mechanized harvesting. The study was carried out at the Nempa - Center for Testing of Agroforestry Machines and Tires (NEMPA) at UNESP/Botucatu. For the tests, the Sugarcane Basal Cut Testing Device (BCTD) was used. The collected data were evaluated using multiple linear regression analysis, using the stepwise method. The results showed that the angulation of the cutting blades is the most significant variable in relation to the impact force generated in the cutting process of sugarcane stalks, this research also managed to assess that the intensity of the angulation effect is more than 2 times greater than the effect generated by the displacement speed in the mechanized harvesting process.